Organic geochemical insights from oil seeps, tars, rocks, and mud volcanoes on the petroleum systems of the Sinú-San Jacinto basin, Northwestern, Colombia. (October 2018) - Cortes, J.E.; Aguilera, R.; Wilches, O.; Osorno, J.F.; Cortes, S.I.
Abstract: Despite the abundance of oil and gas seeps, the Sinú-San Jacinto (SSJ) is an under-explored and poorly understood basin, especially on the dynamics of its petroleum system(s). Recent studies of source rock extracts and oil seeps show that in the Cenozoic sedimentary succession, particularly of Paleocene age, there are intervals with source rock characteristics appropriate for generation of liquid and gas hydrocarbons. Bulk parameters show a medium to highly paraffinic, non-waxy oil seeps with API between 12.69° and 43.17°, sulfur content varying between 0.1100 and 1.6501 wt %. The ™13C isotopic composition of saturate fraction ranges between −28.9 and −22.2‰, while the aromatic fraction has a range of −28.80 to −22.70‰, and C.V. between −5.55 and −0.652, indicating non-waxy marine oils. Most of the samples analyzed by HRGC/FID and SIM-GC/MS in both whole oil and C15 + fractions showed a severe biodegradation process characterized by the total absence of n-alkanes and isoprenoids, the presence of an intense UCM, regular and ââ-steranes in low concentration, and presence of 25-norhopanes. The saturated fraction in condensate and light oil seeps analyzed by GC/FID presents a unimodal distribution between n-C10 to n-C33 with n-C15 to n-C17 as the major peaks. CPI is close or slightly greater than 1.0, Pr/Ph ratio >1.5 indicating an input of algal/microbial organic matter with a significant input of terrestrial matter. Biomarkers showed higher concentration of hopanes over tricyclic terpanes, Ts/Ts + Tm is > 0.25, O.I. ranges between 0.26 and 6.38 suggesting that the organic matter was deposited in a marine or marine deltaic environment during the Tertiary and/or Late Cretaceous. The C26TT/C25 TT ratio indicates both marine and non-marine organic sources. The alternate predominance of sterane distribution between C27- and C29-Steranes indicates that samples have marine, terrestrial or mixed characteristics. Diasterane/Sterane ratio suggests both a carbonate and siliciclastic lithology. Thermal maturity, according to the 20S/20S + 20R-C29 and ââ/áá+ââ-C29 steranes, adamantane and diamantane distribution and aromatic parameters, such as MPI, Rc, %, MNR, MPR, and MDBR indicate a low to moderated maturity. The results obtained indicate that additionally to the Late Cretaceous Cansona Formation, the Paleogene Arroyo Seco Formation could generate liquid hydrocarbons in the basin, and that the Neogene stratigraphic sequence is gas-prone. The presence of multiple potential source rocks for oil and gas generation in the basin open a new spectrum of exploration opportunities in conventional and unconventional petroleum systems associated with the Cenozoic, increasing the potential prospectivity of this under-explored basin. Highlights: Oil seeps, Tars, Impregnated rocks, and mud volcanoes samples from SSJ basin were studied. The potential petroleum systems for Sinu-San Jacinto (SSJ) basin were established. SSJ organic matter origin includes marine algal/microbial with significant terrestrial matter. Organic matter in SSJ basin was deposited in a marine and/or marine deltaic environment during Tertiary and/or late Cretaceous. Biomarkers and aromatic composition in SSJ basin suggest a low to moderated maturity.